Net(h)nographic Analysis of the Impacts of COVID-19 on Tourism in Brazil Análise netnográfica dos impactos do COVID-19 no turismo do Brasil - e Silva D.L.* (2022)
© 2022 PASOS Revista de Turismo y Patrimonio Cultural. All rights reserved.Brazilian tourism has experienced the restrictions on mobility and new rigid health procedures as a result of the COVID-19. pandemic The present research aimed at analysing the impacts of coronavirus on tourism as based on the perceptions of specialists in the area, as given live on the social network Instagram and in interviews. In order to study the impacts, an exploratory qualitative approach was chosen, using the techniques of net(h)nography. Thus, of the results obtained, the study highlights the understanding that post-COVID-19 tourism will recover at a slower pace than other sectors of the economy acquiring formats that privilege domestic tourism, requiring public managers to exercise perspicacity in development and management processes that allow tourist destinations to adapt to the new market demands.